(untitled) (Scientific journal of the Fergana State University, 2023)
Sulfur-containing organic and inorganic compounds are the main harmful component of natural gas and oil, as well as products of their processing. Since sulfur compounds have acidic properties, their content leads to corrosion of technological parts in production processes. The content of hydrogen sulfide in the transported gas should not exceed 20 mg/m3. In Uzbekistan, motor vehicles run mainly on liquefied natural gas. Sulfur compounds in natural gas corrode gas cylinders, resulting in an explosion. If synthetic zeolites are used in manufacturing processes, as well as in small gas production, process degradation will be prevented. Synthetic zeolites are widely used in various industrial production processes due to their high sorption properties. This study makes it possible to study the localization and sorption structure of sulfur compounds in supercavities of zeolites of the faujasite type. The adsorption of hydrogen sulfide on NaX zeolite was carried out in a high vacuum adsorption unit. Based on the results obtained, the differential heat of adsorption, isotherm, entropy, and thermal equilibrium time (thermokinetics) were calculated.